Research methodologies for business management - Ratten, Vanessa (Routledge, 2023)
"Most existing research methodologies texts take a more general approach or are edited books of previously published articles or chapters written by different authors. This book, written by a business management scholar, covers the fundamentals of business management research and its methodologies in a seamless, unified manner. The book offers up-date methodologies and accessible explanations of the research process. It starts with advances in business management research methodology and gives a thorough overview on the different levels of analysis in the field. It builds upon the knowledge by examining both qualitative and quantitative research methodologies in the context of business management. It also goes over the use of machine learning and other technological advances like AI in research and data collection, as well as how the United Nations sustainable development goals are being considered by researchers. This book will help business management students and junior researchers quickly build an essential base of knowledge and gain a strategic advantage in publishing and reviewing business related research"-- Provided by publisher.
Keywords: Industrial management -- Research.; Research -- Methodology.; elektronické knihy; electronic books